Let $H_0=0$
\begin{align}
\sum_{n=1}^{k}\frac{H_n}{n} & = \sum_{n=1}^k\frac{\left(H_{n-1}+\frac{1}{n}\right)}{n}\\
& = \sum_{n=1}^k\frac{H_{n-1}}{n}+\frac{1}{n^2}\\
& = \sum_{n=1}^k\frac{H_{n-1}}{n}+\sum_{n=1}^k\frac{1}{n^2}\\
& = \sum_{n=1}^k\frac{H_{n-1}}{n}+H_{k,2}\\
& = \sum_{n=1}^{k-1}\frac{(H_k-H_n)}{n}+H_{k,2}\\
& = \sum_{n=1}^{k-1}\frac{H_k}{n}-\sum_{n=1}^{k-1}\frac{H_n}{n}+H_{k,2}\\
& = H_kH_{k-1}-\sum_{n=1}^{k}\frac{H_n}{n}+\frac{H_k}{k}+H_{k,2}\\
\therefore 2\sum_{n=1}^{k}\frac{H_n}{n} & = H_kH_{k-1}+\frac{H_k}{k}+H_{k,2}\\